2017
DOI: 10.1016/j.gmit.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Safety of total laparoscopic modified radical hysterectomy with or without lymphadenectomy for endometrial cancer

Abstract: Study objective:In order to reduce the risk of vaginal recurrence, we have chosen total laparoscopic modified radical hysterectomy instead of extrafascial hysterectomy in the treatment of endometrial cancer. The aim of this study was to assess the safety of this method.Design:Retrospective study of gynecological patients.Setting:Yokohama City University Medical Center, Yokohama, Japan.Patients:Forty-nine patients who underwent total laparoscopic modified radical hysterectomy for the treatment of endometrial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This approach offers a means to decrease the morbidity associated with open surgery without compromising oncologic outcome. [ 1 2 3 4 5 6 ] However, the acceptance of laparoscopy for surgical staging women with ovarian cancer remains controversial. Questions remain about the adequacy, feasibility, and standardization of laparoscopic technique, the possible risks of tumor metastases, and impact on survival outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers a means to decrease the morbidity associated with open surgery without compromising oncologic outcome. [ 1 2 3 4 5 6 ] However, the acceptance of laparoscopy for surgical staging women with ovarian cancer remains controversial. Questions remain about the adequacy, feasibility, and standardization of laparoscopic technique, the possible risks of tumor metastases, and impact on survival outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Hematoma formation after laparoscopic surgical staging for endometrial cancer has been reported to be 0.5–2%. [ 1 4 6 7 ] Unlike major vascular injuries that can be catastrophic, hematomas may have a more insidious course. Tinelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…Abscess formation after laparoscopic surgical staging for endometrial cancer has been reported to be ~1%. [ 3 6 7 8 ] In a retrospective study of 30 patients who underwent total laparoscopic hysterectomy and lymphadenectomy for endometrial cancer, one case of pelvic abscess was reported and managed with IV antibiotics and CT-guided drainage. CT-guided percutaneous drainage is an effective, well-established, non-invasive means of treatment of pelvic abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] He has found out that the conceptions of minimally invasive therapy (MIT) for cervical cancer is not the same as those in our study and recent research. [2345678910] Dr. Walker's LAP2 study in 2009 reveals that laparoscopic-assisted staging surgery for endometrial cancer has the same 5-year survival rate as laparotomy. In comparison with laparotomy, laparoscopic-assisted staging surgery for endometrial cancer has much lower hospitalization time, blood loss, and comorbidities.…”
mentioning
confidence: 99%